Race, Class, and Affirmative Action - Fliter, John A. (My University, 2017)
This is an important and timely book on affirmative action. In the landmark US Supreme Court decision University of California, Davis v. Bakke (1978), diversity in college enrollment was recognized as a compelling government interest, and subsequent decisions on the issue have reaffirmed that position. Alon points out, however, that in upholding the value of diversity in higher education, Justice Lewis Powell’s opinion endorsed a concept of “broad diversity” that goes beyond race and ethnicity. The Supreme Court, unfortunately, has been rather vague in defining the components of that diversity.
Citation: Fliter, J. A. (2016). Race, Class, and Affirmative Action. Journal of Politics, 78(3), e5-e6. doi:10.1086/687018
Keywords: Government & Law